Respuesta :

Answer:

10

Step-by-step explanation:

6-3=3 then power of 2 which is 9 then plus 1

Answer:

C

Step-by-step explanation:

Substitute 6 for "x" in (x - 3)² + 1

(6 - 3)² + 1

We now evaluate the expression using PEMDAS

Parenthesis

Exponents

Multiplication and division ( from left to right )

Addition and subtraction ( from left to right )

Step 1: parenthesis

6 - 3 = 3

We would then have (3)² + 1

step 2: exponents

3²=9

we would then have 9 + 1 which = 10

Hence, the answer is C